Strengthening Computational Thinking in Information Technology Education: A Systematic Literature Review on the Development of Higher-Order Thinking Skills - Herianti Herianti; Ayu Widya Listari; Andi Nurqamal Ady Putra; Andi Gagah Purnama; Andi Hasri Tri Ulandari (Jurnal Pendidikan Teknologi, 2026)
The advancement of digital technology necessitates the strengthening of higher-order thinking skills in Information Technology Education (ITE). One approach considered particularly relevant is Computational Thinking (CT), which encompasses processes such as decomposition, pattern recognition, abstraction, and algorithm design. Although numerous studies have examined the implementation of CT in educational contexts, systematic reviews that integrate the relationship between CT and Higher-Order Thinking Skills (HOTS) within the specific context of ITE remain limited and fragmented. This study aims to synthesize the literature on the conceptual construction of CT, analyze its relationship with the development of HOTS, and identify pedagogical implications within ITE learning environments. The method employed is a Systematic Literature Review of national and international articles published between 2015 and 2026, selected through a structured screening process. The findings indicate that CT demonstrates structural alignment with the dimensions of HOTS, particularly in the domains of analysis, evaluation, and creation. However, the effectiveness of CT in enhancing HOTS is conditional and highly dependent on instructional design grounded in authentic problem-solving, explicit reflection, and assessment practices that evaluate thinking processes rather than merely final products. The novelty of this study lies in the integration of CT and HOTS perspectives within a unified conceptual framework specifically tailored to Information Technology Education. These findings provide both theoretical and practical foundations for the development of ITE learning models that are more analytical, reflective, and oriented toward strengthening higher-order thinking skills.